Assessment of The Nurse Interns' Medication Administration Safety Performance - Asmaa S. Saber; Harisa M. A. Elshemy (Evidence-Based Nursing Research)
Contents: Medication administration is an integral part of delivering quality nursing care. The nurse intern should follow the specific guidelines to enhance their medication administration safety.